2011
DOI: 10.1016/j.joca.2011.05.003
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship between fibrogenic TGFβ1 signaling in the joint and cartilage degradation in post-injury osteoarthritis

Abstract: We conclude that progressive articular CA damage in post-injury OA results primarily from biomechanical, cell biologic and mediator changes that promote a fibroblastic phenotype in joint cells. Since ADAMTS5 and TGFβ1 appear to control this process, agents which interfere with their activities may not only enhance endogenous CA repair in vivo, but also improve the properties of tissue-engineered CA for implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 129 publications
6
45
0
2
Order By: Relevance
“…Before drawing conclusions regarding the role of these proteases in the development of posttraumatic OA, these patients will need to be followed over time to evaluate if these MMPs and aggrecan degradation are more strongly correlated with the ultimate development of posttraumatic OA. Prior studies have suggested various cell-signaling mechanisms that may play a role in the development of posttraumatic OA including transforming growth factor-b, endothelin-1, interleukin-1b, and NF-jB [12,15,22,33,37,38]. Our current study should draw attention to the postinjury presence of MMPs and aggrecan degradation as potentially playing a role in progression to OA as well.…”
Section: Discussionmentioning
confidence: 83%
“…Before drawing conclusions regarding the role of these proteases in the development of posttraumatic OA, these patients will need to be followed over time to evaluate if these MMPs and aggrecan degradation are more strongly correlated with the ultimate development of posttraumatic OA. Prior studies have suggested various cell-signaling mechanisms that may play a role in the development of posttraumatic OA including transforming growth factor-b, endothelin-1, interleukin-1b, and NF-jB [12,15,22,33,37,38]. Our current study should draw attention to the postinjury presence of MMPs and aggrecan degradation as potentially playing a role in progression to OA as well.…”
Section: Discussionmentioning
confidence: 83%
“…This may reduce the need for application of growth factors like FGF2, TGFb 1 and PDGFb, which are expensive and have been shown to be associated with degenerative processes in osteoarthritis. 30,33,34,40 To gain an understanding of the mechanistic signaling pathways governing the observed effects of HIFBS treatment to chondrocytes, MAP kinase activity was assessed. It has been established that ERK1/2 activity increases during passage-induced dedifferentiation, 41 and moreover, changes in MAPK signals in general have been correlated with negative effects to chondrocyte phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cell function is associated with the recovery of articular cartilage injury and with the pathomechanism of post-traumatic osteoarthritis [59,60]. In response to injury, MSC within articular cartilage differentiate to produce fibroblastic cells instead of chondrogenic cells.…”
Section: Stem Cells In Chondral Healingmentioning
confidence: 99%